Analisis peran kompetensi karyawan dan kualitas layanan rumah sakit dalam peningkatan kepuasan pasien - Hartati, Leni; Istikomah, Istikomah; Rosadi, Barkah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Advances in digital technology today have brought significant changes in various aspects, especially in the health care industry business. The purpose of this study was to examine the effect of employee competence and the quality of hospital services on patient satisfaction in hospitals in the city of Bandung. This research was conducted in a hospital in the city of Bandung using a sample of 90 patients. The data was then analyzed using a multiple regression analysis approach using SPSS 25 software. The results of this study indicate that partially and simultaneously the variables of employee competence and service quality have a significant influence on patient satisfaction. Based on the results of the coefficient of determination obtained a value of 87.9%. These results indicate that the two variables studied, namely employee competence and service quality have a high enough influence in influencing patient satisfaction at Bandung City Hospital.